Analysis of angiographic characteristics and intervention of vitamin D in type 2 diabetes mellitus complicated with lower extremity arterial disease. (November 2020) - Tan, Jiaojiao; Lv, Haihong; Ma, Yuping; Liu, Chunhua; Li, Qian; Wang, Chenyi
Abstract: Aims: Previous studies have suggested that type 2 diabetes mellitus with lower extremity arterial disease is related to 25-hydroxyvitamin D deficiency. The purpose of this study is to explore the relation between vitamin D supplementation and the characteristics of type 2 diabetes mellitus complicated with lower extremity arterial disease. Methods: The clinical data of 514 patients and 148 healthy subjects treated in the First Hospital of Lanzhou University from January 2012 to June 2019 were collected, including the clinical data, ankle-brachial index, and medical records of lower limb artery angiography. We divided the patients into control group (NC group), type 2 diabetes mellitus group (DM group), lower extremity artery disease in type 2 diabetes mellitus without vitamin D supplement group (DM1 group) and lower extremity artery disease in type 2 diabetes mellitus with vitamin D supplement group (DM2 group). The level of serum 25(OH)D was analyzed and the characteristics of arterial lesions of lower extremities were compared by DSA arteriography in DM1 and DM2 group, respectively. Results: Compared with the NC group, serum 25(OH)D level decreased in DM group (25.39 ± 4.94 ng/mL vs 19.43 ± 5.98 ng/mL) and significantly decreased in DM1 and DM2 group (14.22 ± 5.64 ng/mL vs 17.36 ± 6.25 ng/mL). However, the level of serum 25(OH)D in the DM2 group was higher than that in the DM1 group. Compared with the DM1 group, the disease rate of the inferior knee artery (65% vs 39.3%) and occlusion rate (11.5% vs 3.7%)were decreased in the DM2 group ( P  < 0.05). Logistic stepwise regression analysis showed that serum 25(OH)D level was a risk factor for lower extremity arterial disease in patients with type 2 diabetes mellitus (OR = 0.898, 95%CI = 0.856–0.942). Conclusions: The serum level of 25(OH)D in patients with type 2 diabetes mellitus complicated with lower extremity arterial disease is decreased, and level of 25 (OH) D is related to stenosis and occlusion rate, especially in inferior genicular artery in T2DM complicated with LEAD. A high level of 25(OH)D may be a protective factor in type 2 diabetes with lower extremity arterial disease.